Optimizing Heavy Metal Reduction in Chemical Industry Waste: A Comprehensive Response Surface Methodology Approach for Enhanced Environmental Sustainability - Maria Peratenta Sembiring; Desi Heltina; Chairul Chairul; Sri Rejeki Muria; Melisa Phebeyola Estheria Tarigan (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This study investigates the optimization of heavy metal reduction in solid waste from the chemical industry using Response Surface Methodology (RSM). The Box-Behnken design was employed to optimize the extraction parameters for removing Co, Cu, Pb, and Cr using NaCl as a solvent with Ethylenediaminetetraacetic acid (EDTA) as a chelating agent. The effects of EDTA:Fly Ash ratio, mixing duration, and extraction temperature were evaluated using induced coupled plasma (ICP) and Scanning Electron Microscope and Energy-Dispersive X-ray (SEM/EDS) analysis. NaCl proved effective in reducing Co, Cr, and Pb levels. Optimal conditions for NaCl treatment were identified as an EDTA:Fly Ash ratio of 2:1, 3 hours of mixing time, and an extraction temperature of 52.3 ℃, resulting in a 92.3% total metal reduction. ANOVA results confirmed the statistical significance of the model, with high R² values (0.932 – 0.991) for all metals. The EDTA:Fly Ash ratio and its interaction with mixing duration were found to be the most influential factors in the process. The study demonstrates the effectiveness of RSM in optimizing heavy metal reduction processes and provides insights for improving waste management practices in the chemical industry. The findings highlight the importance of process parameter optimization in enhancing the efficiency of heavy metal removal from industrial solid waste.